2012
DOI: 10.1088/2041-8205/749/1/l16
|View full text |Cite
|
Sign up to set email alerts
|

Time Delays in Quasi-Periodic Pulsations Observed During the X2.2 Solar Flare on 2011 February 15

Abstract: We report observations of quasi-periodic pulsations (QPPs) during the X2.2 flare of 15 February 2011, observed simultaneously in several wavebands. We focus on fluctuations on time scale 1-30 s and find different time lags between different wavebands. During the impulsive phase, the Reuven Ramaty High Energy Solar Spectroscopic Imager (RHESSI) channels in the range 25-100 keV lead all the other channels. They are followed by the Nobeyama RadioPolarimeters at 9 and 17 GHz and the Extreme Ultra-Violet (EUV) chan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 35 publications
(33 reference statements)
6
73
0
Order By: Relevance
“…The scenario of externally triggered QPPs can also clearly explain the time delays between QPPs in different wavelength bands (Dolla et al, 2012). In this scenario, we would have the co-temporal, periodic generation of the non-thermal particles near the X-point.…”
Section: External Oscillatory Triggersmentioning
confidence: 94%
See 3 more Smart Citations
“…The scenario of externally triggered QPPs can also clearly explain the time delays between QPPs in different wavelength bands (Dolla et al, 2012). In this scenario, we would have the co-temporal, periodic generation of the non-thermal particles near the X-point.…”
Section: External Oscillatory Triggersmentioning
confidence: 94%
“…Having multiple harmonics in the loop, would then also naturally explain the multiple harmonics seen in the QPPs. In this theory, it is not very obvious how time delays between different wavelength bands may be explained (Dolla et al, 2012).…”
Section: Mhd Waves In Flaring Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that both energetic electrons and ions are accelerated in the same process. Time delays between emission peaks have also been found from observations at different wave bands, which could be caused by trap or escape processesof energetic electrons at different energy bands (Aschwanden et al 1997;Dolla et al 2012;Tsap et al 2013). Huang et al (2014) found QPPs with varying periodsin multi-wavelength observations in an X class flare.…”
Section: Introductionmentioning
confidence: 87%